Perpustakaan Digital Berbasis Website pada SMP Negeri 15 Tanjungpinang - Zulfachmi Zulfachmi; Revanda Fitra Inanta (Jurnal Bangkit Indonesia, 2022)
The digital library is one of the supports in the world of education to search for information using information technology and the internet. General problems that occur in libraries such as data availability, library member data, borrowing book data, book data, and school reports can be overcome with availability related to the use of information technology. The author likes the development of this digital library with the library of SMP Negeri 15 Tanjungpinang. In searching for information on digital library development, the authors conducted observations and interviews with the library of SMP Negeri 15 Tanjungpinang so that the features developed in the digital library were in accordance with the wishes of the users. Digital library application development uses the laravel framework so that application development is faster and safer. The features developed in this application are book data collections, book details, librarians, library member pages, book borrowing pages, book collection pages, as well as various reports intended for libraries and schools at SMP Negeri 15 Tanjungpinang. In the application testing process, the author uses the blackbox testing method. The results of this study provide convenience for librarian in managing library data online. In addition, librarian becomes easier in the latest information on the availability of managed book data, ease in managing library member data, ease in managing library data and book data, as well as preparing reports addressed to the school..